Prioritising indigenous representations of geopower: the case of Tulita, Northwest Territories, Canada - Perombelon, B (2018)
Recent calls from progressive, subaltern and postcolonial geopoliticians to move geopolitical scholarship away from its Western ontological bases have argued that more ethnographic studies centred on peripheral and dispossessed geographies need to be undertaken in order to integrate peripheralised agents and agencies in dominant ontologies of geopolitics. This thesis follows these calls. Through empirical data collected during a period of five months of fieldwork undertaken between October 2014 and March 2015, it investigates the ways through which an Indigenous community of the Canadian Arctic, Tulita (located in the Northwest Territories’ Sahtu region) represents geopower. It suggests a semiotic reading of these representations in order to take the agency of other-than/more-than-human beings into account. In doing so, it identifies the ontological bases through which geopolitics can be indigenised. Drawing from Dene animist ontologies, it indeed introduces the notion of a place-contingent speculative geopolitics. Two overarching argumentative lines are pursued. First, this thesis contends that geopower operates through metamorphic refashionings of the material forms of, and signs associated with, space and place. Second, it infers from this that through this transformational process, geopower is able to create the conditions for alienating but also transcending experiences and meanings of place to emerge. It argues that this movement between conflictual and progressive understandings is dialectical in nature. In addition to its conceptual suggestions, this thesis makes three empirical contributions. First, it confirms that settler geopolitical narratives of sovereignty assertion in the North cannot be disentangled from capitalist and industrial political-economic processes. Second, it shows that these processes, and the geopolitical visions that subtend them, are materialised in space via the extension of the urban fabric into Indigenous lands. Third, it demonstrates that by assembling space ontologically in ...